Meaning Search of Agricultural Technology Terms Internet Based-Learning in Translation and Learning English - I Gusti Agung Istri Aryani; Made Detriasmita Saientisna; Ni Putu Evi Wahyu Citrawati (Basic and Applied Education Research Journal, 2022)
The current development of technology has been instantly changing the whole society with the easy access for searching information through the internet. Using media support is a consideration to increase activities of learning and adapting the development of this era. The English learning desire creativity for teaching the students as their target goal. This research aims to analyze the meaning of the terms related to science agricultural technology by implementing Internet Based-Learning for students in the Department of Food Technology, including their translation. It was conducted with mixed methods (qualitative and quantitative). by giving guidance to first-year semester on how they could use the WebCorp media to search articles. Then, students instructed to find the translation and understanding of the meaning in each of the terms. This search engine is a machine that compiles Bing or big data capacity and collected as corpus. The texts can be found in various types and sources on the internet. The discussion of problems in the study covers description of understanding the meaning search for terms related to agricultural technology, evaluating parameter of ability to search meaning through internet based-learning by using WebCorp media and strategies implementation to learn English, mainly meaning related to agricultural technology. It showed that there were 47 terms equivalence based on their English terms meaning and translation of Indonesian related to agricultural technology, meanwhile, 7 were found inequivalence for their meanings and text chosen. So, 87% of their results relevant to the agricultural technology but 13% were not connected with the specification of terms and meaning. The students understood how to use the media of searching and gave experience to them.